IN SEARCH FOR ETHICAL RELATIONS IN SOCIAL WORK WITH REFUGEES COMMUNITIES: REFLECTIONS ON THE SYRIAN REFUGEE “CRISIS” - Nobe-Ghelani, Chizuru; Ngo, Anh (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
For this conceptually oriented paper, we examine the politics of Canadian humanitarianism in refugee resettlement and its relationships to everyday social work practice with refugees. We argue that Canada’s refugee resettlement efforts have functioned to construct a particular refugee identity while confirming itself as a humanitarian nation-state. This constitutive identity construction of refugee and Canada have effectively concealed Canada’s historical and ongoing settler colonial violence, its complicity in the Middle East conflict, as well as its racist refugee policy regime. We suggest that, despite the profession’s orientation towards social justice, social work has been complicit in these problematic identity constructions. As a profession shaped by a historical investment in whiteness, social work remains complicit in the Othering as long as we hold onto our identity as professional helpers. This paper discusses the possibility of disrupting the investment in whiteness as a way to create a condition for ethical engagement with refugee populations.